Effect of inter-adatoms correlations on the local density of states of graphene - Seridonio, A. C. [UNESP]; Kristinsson, K.; Souza, M. de [UNESP]; Souza, F. M.; Guessi, L. H. [UNESP]; Machado, R. S. [UNESP]; Shelykh, I. A. (Epl Association, European Physical Society, 2014)
We discuss theoretically the local density of states (LDOS) of a graphene sheet hosting two distant adatoms located at the center of hexagonal cells. By putting laterally a scanning tunneling microscope (STM) tip over a carbon atom, two remarkable novel effects can be detected: i) a multilevel structure in the LDOS and ii) beating patterns in the induced LDOS. We show that both phenomena occur nearby the Dirac points and are highly anisotropic. Furthermore, we propose conductance experiments employing STM as a probe for the observation of such exotic manifestations in the LDOS of graphene induced by inter-adatoms correlations. Copyright (C) EPLA, 2014